Entrepreneurship - Hisrich, Robert D.; Peters, Michael P.; Shepherd, Dean A. (Dubuque, IA : McGraw Hill LLC, 2024)
"Starting and operating a new business involves considerable risk and effort to overcome the inertia against creating something new. In creating and growing a new venture, the entrepreneur assumes the responsibility and risks for its development and survival and enjoys the corresponding rewards. This risk is compounded for entrepreneurs who go international or who are in fact born global. The fact that consumers, businesspeople, and government officials from every part of the world are interested in entrepreneurship is evident from the increasing research on the subject, the large number of courses and seminars on the topic, the more than two million new enterprises started each year (despite a 70% failure rate), the significant coverage and focus by the media, and the realization that this is an important aspect of the economics of the developed, developing, and even controlled economies"--
Revised edition of the authors' Entrepreneurship, [2020]
Includes index.
Ages 18+
Grades 10-12
Keywords: New business enterprises; Entrepreneurship; Business planning; Business enterprises -- Finance; Success in business